Ground measurements of the Earth Electric Field - BRESSAN, GIORGIO; GENNARO, VALTER; GIAIOTTI, DARIOB.; STEL, FULVIO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2004)
This work provides a description and physical interpretation of the Earth’s electric field over the plain of Friuli. The electric field is measured by way of a field mill positioned in Ziracco (UD). The field mill records the changes of the electric field every second, both in fair weather and stormy conditions. In fair weather conditions the Earth electric field points toward the ground and has values of the order of 100 Vm-1. In stormy conditions, the Earth electric field magnitude increases rapidly and sudden inversions take place during the atmospheric electrical discharges. After these discharges the electric field returns to its initial values in different ways that still need an exhaustive interpretation. At the end of the storm, a typical trend is revealed. This trend can be interpreted based on the simple tripole model. All these features are analyzed in conjunction with the radar data, in particular with the VMI measurements, and in conjunction with the position of the cloud to ground lightning strikes.